Isomorphic pressures and XBRL adoption: a meta-analysis with economic level as a moderator - Mona Permatasari Mokodompit; Bambang Subroto; Sutrisno T.; Imam Subekti (Cogent Business & Management)
This study aims to examine the impact of isomorphic pressures (coercive, normative, and mimetic) on the adoption of eXtensible Business Reporting Language (XBRL), with the economic level as a moderator. We employ a meta-analysis approach to synthesize 138 outcomes from articles published between 2010 and 2024. The findings indicate that isomorphic pressures, particularly mimetic pressures, affect XBRL adoption. The economic level of a country has a moderating influence, and developed countries are more susceptible to normative demands. This study expands institutional theory by revealing the varied effects of isomorphic pressures on technology adoption in different economic contexts and introducing a nuanced theoretical framework of understanding technological adoption. The findings offer practical insights for policymakers to design institutional settings that include regulatory mandates, financial incentives, and technical support, and for business leaders regarding the execution of successful strategies.